Performing the literary map: 'towards the river mouth' following Gianni Celati. (July 2017) - Peterle, Giada; Visentin, Francesco
This article retreads our geographic and literary performance in March 2015, following, almost 30 years later, the traces of Gianni Celati's travel diaries Verso la foce ('Towards the River Mouth') through the Po River Delta, in Northeastern Italy. In our reading of Celati's text and during our 2-days performance, we decided to 'go along' the Po River, considered as a 'liquid chronotope' that discloses and shapes a geographic and narrative 'liquid landscape'. We moved 'from text to action' and, interpreting literary maps 'as always mappings', we performed the 'implicit map' that emerges from Celati's travel diaries. The purpose of the article is to re-activate the geographic understandings of Po River Delta's waterscape: through our performance, we aimed to re-read Celati's literary/geographical observations for interpreting the transformations of this peculiar Italian landscape. Moreover, the perspective of a photographer enhances the narration of the performance to open up the readers to further 'visions' of the Po River Delta.